South American sea lions (Otaria flavescens) avoid killer whale (Orcinus orca) predation - Vila, Alejandro R.; Campagna, Claudio; Iñiguez, Miguel; Falabella, Valeria (Aquatic Mammals)
South American sea lions (Otaria flavescens) are predictably preyed on by killer whales (Orcinus orca) at their breeding colonies in Peninsula Valdés, Argentina. Captures occur in shallow waters along the coastline. Killer whales strand in the surf where sea lion pups practice their swimming skills. Being slow and apparently unaware of danger (nonvigilant), pups are the most vulnerable prey (87% of captures). Adult sea lions escaped most attacks by increasing their swimming speed, changing directions swiftly, grouping, and hauling out of the water. In our observations, predator avoidance behaviours were contextual and based on the presence of killer whales and the degree of risk in the areas used by sea lions during their movements between rookeries. Swimming speed increased in sites where the risk of predation was highest and when killer whales were present. Vigilance and escape manoeuvres were recorded at these dangerous sites, characterized by deeper water and a sloping beach, which allowed the killer whales to strand or approach the coast safely. Predictability of the killer whales in space and time facilitates the South American sea lions in developing a reliable antipredation behaviour. Killer whales become more proficient at being predators, and adult sea lions become better at avoiding being preyed upon as they accumulate experience. The inexperience of the sea lion pups is the currency that sustains the killer whale's high rate of take. Fil: Vila, Alejandro R. Wildlife Conservation Society; Argentina Fil: Campagna, Claudio. Wildlife Conservation Society; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Nacional Patagónico; Argentina Fil: Iñiguez, Miguel. Fundación Cethus; Argentina Fil: Falabella, Valeria. Wildlife Conservation Society; Argentina